Anais Estendidos Do XX Simpósio Brasileiro De Jogos E Entretenimento Digital (SBGames Estendido 2021) 2021
DOI: 10.5753/sbgames_estendido.2021.19749
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Pedagogy, Emotions and Game Design in Serious Game Development

Abstract: Serious games and game-based learning approaches have been shown to provide effective learning outcomes in various contexts. However, the design of games with educational purposes is not an easy feat, since many aspects must be considered during development: pedagogical theories, learning mechanics, game elements, player experience, and affective, cognitive and behavioral outcomes. The balance of these aspects is one of the greatest challenges both game designers and educators must face in the next few years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The scenario of the game and the perceived short-term learning were positively evaluated with the vast majority of the participants stating that they agree or strongly agree that all the corresponding items were successfully implemented. The aforementioned results showed that SpAI War achieved a good balance between pedagogy and entertainment/fun, which is considered to be one of the most challenging aspects in designing serious/educational games [12][13][14][15]. In our opinion, this can be attributed to the way that the educational material was integrated into the scenario of the game.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The scenario of the game and the perceived short-term learning were positively evaluated with the vast majority of the participants stating that they agree or strongly agree that all the corresponding items were successfully implemented. The aforementioned results showed that SpAI War achieved a good balance between pedagogy and entertainment/fun, which is considered to be one of the most challenging aspects in designing serious/educational games [12][13][14][15]. In our opinion, this can be attributed to the way that the educational material was integrated into the scenario of the game.…”
Section: Discussionmentioning
confidence: 89%
“…In order to achieve this, we decided to evaluate the game in terms of player experience, the scenario of the game and the perceived short-term leaning of the AI algorithms incorporated in the game. The aforementioned evaluation data would give us the chance to investigate whether the factors that are considered important for serious game design were successfully implemented, and a balance between pedagogy and fun was achieved [11][12][13][14][15]. Consequently, the following research question was investigated:…”
Section: Research Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants consider that the educational content of the game (median = 4) is relevant to its purpose and without errors; fits the characteristics of its target group; and the main principles of safe Internet use. What is more important is that the participants agree that there is a balance between game elements and the achievement of the educational objective of the game (median = 4), which is widely accepted to be a great challenge for educational games [16,17]. The tasks within the game are considered to be appropriate to the educational background of primary school students (median = 4), while the game provides scaffolding features.…”
Section: Game Acceptance and Didactic Utility (Rq1)mentioning
confidence: 99%